Comercio de Mercancías Locales en Santiago de Chile, 1773-1778 - Martinez-Barraza, J (Cambridge University Press, 2021)
This article deals with the trade of local merchandise in Santiago s district (Corregimiento) from 1773 to 1778, based on tributary sources. It contributes to the debate on the organization of the colonial internal market. The main traded merchandise, which represented about 80% of Chilean exports, came from the cattle exploitation that was developed in the haciendas around Santiago, whose cattle stocks were complemented from neighboring provinces in the Andes. The largest destination of this trade, in which big merchants acted together with a thousand minor merchants, were the retail channels and the artisan sectors supplying the population of Santiago. The impulse of this demand on the domestic market was so dynamic that it shows a degree of regional autonomy higher than what it is traditionally assumed for the Chilean economy in the late colonial period. Copyright © Instituto Figuerola, Universidad Carlos III de Madrid, 2019.